ERM Ideas & Innovations. Issue 3 (3rd July 2017) - England, Lenore; Lowe, Randy; Owusu, Erica
ABSTRACT: University System of Maryland & Affiliated Institutions (USMAI) e-resources librarians and staff, the authors of this column, developed a consortial governance framework, through an incubator process, to essentially increase shared consortial e-resources collection development and reap the beneficial results of a more refined, honed effort in the process. At the time the authors established the framework in 2015, USMAI was not a recognized legal entity, had no procurement or signatory central authority, no dedicated staff, and no budget specifically for e-resources. The authors discuss how the framework has actualized and changed circumstances since 2015 and how the incubator approach has worked, and offer perspectives on the future of the framework, which is essential to ongoing strategic planning.